Management of digital mutation within West-African financial ecosystem. Collaboration and reciprocity of skills : improvement of financial services in Benin - (:unkn) unknown (My University, 2021)
Digitalization has become ineluctable and is a reference key in business processes around the world. It does not matter how it is named: numerical revolution or transition, it is disrupting markets’ organizational structures, business processes and global supply chain. Digitalization process is common in business; however, digital practices are unique to each geographic area. Consumers’ behaviors have evolved along with new technologies and banks have to adjust to financial technologies’ (FinTech) disruptive innovations under a harsh banking prudential regulatory context. These innovations have deeply affected strategic growth and collaboration within West-African financial ecosystem.As a result, all financial institutions, FinTech firms, and Mobile Network Operators (MNO) come together to design cooperative models that will allow them to maintain their different competitive advantages, by fulfilling their social and environmental responsibility and improve financial inclusion. It is of interest to discover how the cooperation among different partners will allow West-African financial ecosystem to be more inclusive by exploring collaborative opportunities among banks, FinTech firms, and MNO that will be a measuring tool of open banking enhanced by the digitalization of the financial sector and to analyze the value created by this cooperation among the partners mentioned above.
Keywords: African Research